Assessment of pulmonary function test in type 2 diabetes mellitus and its correlation with their HbA1c levels - Toppo, Archana; Ajamani, Kulvant Singh (International Journal of Advances in Medicine, 2019)
Background: Diabetes mellitus (DM) is a group of metabolic disorders characterized by hyperglycemia and deranged metabolism of carbohydrates, lipids and protein that result from insensitivity to endogenous insulin. It is a substantial global health problem and markedly increases morbidity and mortality of the affected people. Methods: The present study was conducted in the Department of medicine Dr. B.R.A.M. Hospital, Raipur. Total 67 subjects with type II diabetes mellitus as per WHO criteria of diabetes mellitus, aged between 18-60years of both sexes were included in the study. Patients FBS, PPBS were analysed by glucose oxidase (GOD), peroxidase (POD) methods in ILAB 650 analyser and HbA1C was analysed using HPLC. Pulmonary function test was conducted in all the subjects using the spirometer which is the gold standard for accurate and repeatable measurement of lung function. Results: Majority of the subjects were male (36, 53.7%) and belonged to age group of 51-60years (n=34, 50.7%), Duration of DM </=10years (n=47, 70.1%), restrictive pulmonary function in 10 (14.9%) subjects. Correlation of age with a restrictive pattern of PFT (P=0.013*) and with duration of diabetes (P<0.0001**). Pulmonary function test parameters having mild downstream correlation with diabetes mellitus. Conclusions: Diabetes was more common in the sixth decade of life with slight male preponderance. The short-term indicators of glycaemic controls were not significantly associated with a restrictive pattern of PFT. Despite the best effort, there are limitations of this study, which includes small sample size, author have not taken general population, and lack of a control group. These limitations can be overcome in the future studies.